The antigen receptors on mature and immature T lymphocytes are coupled to phosphatidylcholine-specific phospholipase D activation. - Reid, P A (1997)
Phosphatidylcholine-phospholipase D has been proposed to play a key role in the transduction of the proliferative responses of a wide range of mitogens and growth factors. We now report that the antigen receptors on T lymphocytes derived from human tonsillar or murine splenic preparations are coupled to phosphatidylcholine (PtdCho)-phospholipase D (PLD) activation following stimulation of these T cells with anti-CD3 antibodies. However, since we also demonstrate that the antigen receptors on murine thymocytes are coupled to PtdCho-PLD activation, we propose that it is unlikely that this PLD pathway plays a central role in the transduction of T-cell proliferative responses, but rather, may be involved in either driving cells into cycle or maintaining cell cycle progression, processes required both for proliferation and activation-induced cell death. Whilst the molecular mechanisms underlying T-cell receptor (TCR)-coupling to PtdCho-PLD activation in these cells have not been fully defined, kinetics studies and experiments using pharmacological inhibitors of protein tyrosine phosphatases (PTPases) and reconstituting CD3-coupled PtdCho-PLD activity in streptolysin-O permeabilized cells, suggest that the TCR/CD3 complex, under optimal conditions of activation, may be predominantly coupled to PtdCho-PLD activation downstream of tyrosine phosphorylation of phospholipase C-gamma (PLC-gamma), phosphatidylinositol (PtdIns)P2 hydrolysis, calcium mobilization and protein kinase C (PKC) activation.